PEMANFAATAN ALAT PERAGA UNTUK MENINGKATKAN PEMAHAMAN IKATAN HIDROGEN: SOSIALISASI VISUAL DNA DI SMAK MENARA TIRZA - Illya, Gregoria; Anita, Novia; Zendrato, Kent Juan Nataniel Yaoisokhi (Universitas Sanata Dharma, 2025)
Community service is one of the three pillars of higher education, alongside education and research, which aims to bring scientific knowledge directly to the community. This community service activity was conducted through an interactive socialization program on hydrogen bonding in DNA for students at SMA Kristen Menara Tirza. The program utilized a visual teaching aid developed by the Physics Study Program at Matana University to support understanding of abstract molecular structures such as the DNA double helix. The activity involved presentations, hands-on demonstrations, and two-way discussions using the teaching aid. Thirteen students from grade 12 participated in the session, which included pre-tests and post-tests to evaluate learning outcomes. The average test score increased from 35.38 to 55.38, indicating an improvement. Based on this result, all students agreed or strongly agreed that the teaching team mastered the material and presented it engagingly and that the activity was beneficial to their learning. This program shows that a socialization method supported by visual teaching aids significantly improves student comprehension of complex scientific concepts. It is recommended that similar programs be implemented more widely and supported with the development of digital or interactive learning tools to reach broader audiences.